Estimating the abundance of Nepal's largest population of tigers Panthera tigris. Issue 1 (January 2015) - Karki, Jhamak B.; Pandav, B.; Jnawali, S. R.; Shrestha, R.; Pradhan, N. M. B.; Lamichane, B. R.; Khanal, P.; Subedi, N.; Jhala, Y. V.
Abstract Information on the abundance of tigers Panthera tigris is essential for effective conservation of the species. The main aim of this study was to determine the status of tigers in Chitwan National Park, Nepal, including the Churia hills, using a camera-trap based mark–recapture abundance estimate. Camera traps (n = 310) were placed in an area of 1, 261 km2 from 20 January to 22 March 2010. The study area was divided into three blocks and each block was trapped for 19–21 days, with a total effort of 3, 582 man-days, 170 elephant-days and 4, 793 camera-trap nights. The effectively camera-trapped area was 2, 596 km2. Camera stations were located 1.5–2 km apart. Sixty-two tigers (age ⩾ 1.5 years), comprising 15 males, 41 females and six of unidentified sex, were identified from 344 photographs. The heterogeneity model Mh (jackknife) was the best fit for the capture history data. A capture probability (<alternatives><inline-graphic xlink:href="ark:/27927/pgj46pt2bf" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> <![CDATA[$\hat P$]]> </alternatives>) of 0.05 was obtained, generating a population estimate (<alternatives><inline-graphic xlink:href="ark:/27927/pgj46pt1bz" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> <![CDATA[$\hat N$]]> </alternatives>) of 125 ± SE 21.8 tigers. The density of tigers in the area, including Churia and Barandabhar (buffer zone forest linked with mid hill forest), was estimated to be 4.5 ± SE 0.35 tigers per 100 km2, using a Bayesian spatially explicit capture–recapture model in SPACECAP. Our study showed the use of Churia by tigers and we therefore conclude that the Chitwan tiger population serves as a source to maintain tiger occupancy of the larger landscape that comprises Chitwan National Park, Parsa Wildlife Reserve, Barandabhar buffer zone, Someswor forest in Nepal and Valmiki Tiger Reserve in India.